Metaphorical Perceptions of Academicians and Engineers on the Conceptions of Game and Exercise: The Case of Boston, Massachusetts - Hacer Ozge Baydar Arican, (Journal of Educational Issues, 2024)
Games and exercises, which have an important place in the life of the individual in every developmental period of humans as a social being contribute to the communication and interaction of the individual with the environment, to the development of social cognitive skills such as problem-solving, analytical thinking, creative thinking, and reasoning as well as positively affecting the physical and mental development. Individuals, who try to survive in a mentally and physically challenging and demanding work pace or by being inactive for a long time in front of a computer screen, spend their energy through games, exercises, and physical activities, and can be discharged by relaxing. In this respect, it is possible to evaluate the entire games, exercises, and physical activities as a driving force to gather energy again after a tiring work tempo or as a source of motivation to move away from mental and physical fatigue. It is considered that performing activities such as exercises and playing games by individuals, considering them as a way of life and evaluating the factors, which keep individuals away from these activities, can be possible by explaining individual perceptions on these issues. In the light of these data, the meanings and values associated with the concepts of games and exercises by academics and engineers who live in different cultural structures, who cannot allocate adequate time for games and exercises in a compulsory work tempo, or who can acquire internal and external motivation via games and exercises as well as exercise frequency and playing times. The present study was conducted to examine the perceptions of academics and engineers on the concepts of game and exercise via metaphor analysis in June 2019 with the participation of scientists, academicians, and engineers who participated in the 2019 International Microwave Symposium (IMS) at the Boston Convention and Exhibition Center in Boston, MA, USA, which was held with the participation of many scientists, academicians, and engineers from all over the world as a total of 135 participants, 56 women and 79 men, who agreed to participate in the study voluntarily, made up the study group. The metaphor analysis form that was prepared by the researcher was used in obtaining the data to reveal the perceptions of the participants about the concepts of game and exercise. The participants were asked to complete the statements with the statements of “Game is like … because …” and “Exercise is like … because …” in addition to their age, gender, nationality, residence, occupation, perceived income status, and educational status. After the data were analyzed, various metaphors for the concepts of game and exercise were detected. Also, different game playing times and exercise frequencies emerged as a result of the self-evaluation of each participant.